Tinjauan Anatomi Klinik dan Manajemen Bell's Palsy - Nur Mujaddidah (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2017)
Bell's Palsy is a peripheral facial nerve weakness (facial nerve) with acute onset on one side of the face. This condition causes the inability of the patient to move half of his face consciously (volunter) on the affected side. The Bell's Palsy incidence is 20-30 cases out of 100.000 people and accounts for 60-70% of all cases of unilateral facial paralysis. The disease is self-limited, but causes great suffering for patients who are not treated properly. Controversy in the management is still debated, and the cause is still unknown. The underlying hypothesis is ischemic, vascular, viral, bacterial, hereditary, and immunologic. Therapy done so far is to improve facial nerve function and healing process. The management of the therapy used will be closely related to the structure of the anatomy and its functions and associated abnormalities. The modalities of Bell's Palsy therapy are with corticosteroids and antivirals, facial exercises, electrostimulation, physiotherapy and decompression operations. Approximately 80-90% of patients with Bell's palsy recover completely within 6 months, even in 50-60% of cases improved within 3 weeks. Approximately 10% experienced persistent facial muscle asymmetry, and 5% experienced severe sequelae, and 8% of cases were recurrent.